2022
DOI: 10.3390/cancers14123006
|View full text |Cite
|
Sign up to set email alerts
|

Patient Derived Ex-Vivo Cancer Models in Drug Development, Personalized Medicine, and Radiotherapy

Abstract: The field of cancer research is famous for its incremental steps in improving therapy. The consistent but slow rate of improvement is greatly due to its meticulous use of consistent cancer biology models. However, as we enter an era of increasingly personalized cancer care, including chemo and radiotherapy, our cancer models must be equally able to be applied to all individuals. Patient-derived organoid (PDO) and organ-in-chip (OIC) models based on the micro-physiological bioengineered platform have already be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…The molecular biology of sarcomas is poorly understood, especially the interplay among signaling pathways, as well as the epigenetic modifications and regulatory RNA sequences. Patient-derived 3D sarcoma models could be useful to recapitulate the three-dimensional structure of these neoplasms, clarifying the complex crosstalk between tumor cells and their microenvironment, and contributing to personalized medicine development [7,53].…”
Section: Established Cancer-derived Cell Linesmentioning
confidence: 99%
“…The molecular biology of sarcomas is poorly understood, especially the interplay among signaling pathways, as well as the epigenetic modifications and regulatory RNA sequences. Patient-derived 3D sarcoma models could be useful to recapitulate the three-dimensional structure of these neoplasms, clarifying the complex crosstalk between tumor cells and their microenvironment, and contributing to personalized medicine development [7,53].…”
Section: Established Cancer-derived Cell Linesmentioning
confidence: 99%
“…Up to 50% of these failures are due to lack of clinical efficacy, which can be interpreted as a lack of pre-clinical models that accurately reflect in vivo response [ 9 , 10 ]. Given its ability to mimic the 3D multicellular architecture of human disease, the ex vivo patient-derived explant (PDE) culture technique has recently emerged as a powerful preclinical platform for cancer research [ 11 ]. PDEs are typically small (1–3 mm in diameter) pieces of fresh tumour that are cultured without disintegration into the tissue’s individual cellular components.…”
Section: Introductionmentioning
confidence: 99%
“…Although 2D monolayer cancer-derived cells are often used in imaging assays (31), there are conflicting reports of their limited expansion potential. Jeppesen et al conducted a comparative study of colorectal cancer cell extraction and cultivation procedures as monolayer cultures (32) and concluded that trypsin was the best method to digest the tissue.…”
Section: Introductionmentioning
confidence: 99%